Religious Movement of Buddhadāsa: Reformation and Development of Thai Buddhism - Barua, Pranab (The Journal of International Buddhist Studies College, 2019)
Buddhadāsa Bhikkhu (1909-1993) both nationally and internationally is the most famous Thai monk. His movement is one of the most prominent religious movements in contemporary Thailand. This movement played a prominent role in the development of Thai Buddhism throughout the mid part of the 19th and the end part of the 20th century. The central feature of the movement lies in the reinterpretation of Pāli Canon by Buddhadāsa Bhikkhu. Buddhadāsa interprets the Theravada doctrine intellectually and critically. His interpretation of Buddhism refl ects not only the potential of traditional religious culture to accommodate to modern life but also impels Buddhism toward modernization.